(untitled) (Research, Society and Development, 2022)
Within current clinical practice, the concomitant association of multiple drugs for the treatment of chronic pathologies is a common procedure in the therapeutic drug experience. In which the complex and diverse clinical laboratory routine can be influenced by the existence of drug interference. From this perspective, through a bibliographic research of the integrative review type in the databases of the Virtual Health Library, using the insertion of the DeCS: Pharmaceutical Preparations/Pharmaceutical Preparations, Drugs, (Hematological test), combined with the help of the Boolean operator "AND", the present study sought to describe, based on the current literature, the laboratory changes caused by the use of medicines in the results of blood tests of patients. From the interpretation of the data, synthesized by the review, it was observed that the three drugs with the highest numbers of repressions in the results of blood test parameters were Methylphenidate, Capecitabine and Clozapine. Therefore, during clinical practice, biomedical professionals become fundamental pieces for carrying out an adequate analysis of changes in biochemical markers caused by medications.